Do you mean 3x2+10x-8 if so then it is (3x-2(x+4) when factored
(x + 4)(3x + 35)
It is a quadratic expression and can be factored into: (3x+1)(x+2)
13
-3x2+10x-3 -(3x2-10x+3) -(3x-1)(x-3)
Do you mean 3x2+10x-8 if so then it is (3x-2(x+4) when factored
-(3x - 4)(x - 2)
(x + 5)(x - 8)
-(3x+4)(x+2)
It is: (-3x-4)(x+2) when factored
3x3 - 24x2 + 45x = 3x*(x2 - 8x + 15) = 3x*(x - 3)*(x - 5)
3x3-18x2+24x=3x(x2-6x+8)=3x(x-4)(x-2)
3x3 - 24x2 + 45x = 3x(x2 - 8x + 15) = 3x(x2 - 3x - 5x + 15) = 3x[ x(x - 3) - 5(x - 3) ] = 3x(x - 5)(x - 3)
No. It is 9x, which is a monomial.
6xyz(3x + 2y + z)
33(3x - 2y + z)
9x+3